The improtance of the sphincterotomy in the diagnosis of periampullary carcinoma: analysis of 664 patients who underwent ERCP - Yusuf BAYRAKTAR; Ahmet ÖZGENÇ; Arif ÖZDEMİR and Gürol ÖKSÜZOĞLU and Serap ARSLAN and Teoman COŞKUN and Bedri UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2019)
-